Medical Treatment of Cystoid Macular Edema with Topical Steroids and Topical Non-Steroidal Anti-Inflammatory Drugs - Salim, Mahmoud A.; Diab, Rawya A.; Ahmed, Sana; Alhassan, Zuhal (Gezira Journal of Health Sciences, 2014)
Aim: To provide knowledge that topical steroids and topical non-steroidal antiinflammatory drugs "NSAIDs"; can cure cystoid macular edema "CME"; which is currently mostly treated by invasive procedures "i.e. intravitreal steroids and anti VEGF, laser and vitrectomy". Introduction : Through many years ever since the CME has been discovered by Irvin, invasive interventions were regarded as the most effective curative modalities of treatment. Recently it was proved that there is an inflammatory reaction in the process of CME formation, based on that evidence many studies started aiming at evaluating the role of anti-inflammatory agents in the treatment of CME. Case presentation: A 60 years old gentleman presented with deterioration of vision in his right eye over 45 days, he is on antiglaucoma medications and has undergone a glaucoma surgery two years back, there were no any associated systemic symptoms or diseases. On examination: the left eye was diagnosed as end stage glaucoma and so it was excluded from the examination; on examination of the right eye: best corrected visual acuity was 6/36; intra ocular pressure "IOP" 10 mmHg, dilated fundus examination: Optic disc: glaucomatous atrophy, Vessels: attenuated arterial system and congested venous system, Macula: dull with irregular slit lamp light appearance indicating microcysts formation; and Periphery: was non informative, Ocular Coherent Tomography "OCT": showed marked increased thickness of the retinal layers with cysts formation at the macular area. Accordingly the patient was diagnosed as cystoid macular edema and hence the plan was to put him on topical steroids and topical NSAIDs eye drops qid, a regular follow up and measurement of IOP. Results: OCT repeated after a month and there were no obvious changes, four months later OCT showed a remarkable improvement; i.e. the thickness is much lesser, another OCT after a further month showed complete resolution of the edema, and best corrected visual acuity was 6/24. Discussion and Conclusion: CME is in part an inflammatory condition; so it could possibly be treated with anti-inflammatory agents, such as topical steroids and NSAIDs, as it is evident in this case CME can be totally cured without the need of invasive procedures.